Enrichment of G4DNA and a Large Inverted Repeat Coincide in the Mitochondrial Genomes of Termitomyces. (18th June 2019) - Nieuwenhuis, Mathijs; van de Peppel, Lennart J J; Bakker, Freek T; Zwaan, Bas J; Aanen, Duur K
Abstract: Mitochondria retain their own genome, a hallmark of their bacterial ancestry. Mitochondrial genomes (mtDNA) are highly diverse in size, shape, and structure, despite their conserved function across most eukaryotes. Exploring extreme cases of mtDNA architecture can yield important information on fundamental aspects of genome biology. We discovered that the mitochondrial genomes of a basidiomycete fungus ( Termitomyces spp.) contain an inverted repeat (IR), a duplicated region half the size of the complete genome. In addition, we found an abundance of sequences capable of forming G-quadruplexes (G4DNA); structures that can disrupt the double helical formation of DNA. G4DNA is implicated in replication fork stalling, double-stranded breaks, altered gene expression, recombination, and other effects. To determine whether this occurrence of IR and G4DNA was correlated within the genus Termitomyces, we reconstructed the mitochondrial genomes of 11 additional species including representatives of several closely related genera. We show that the mtDNA of all sampled species of Termitomyces and its sister group, represented by the species Tephrocybe rancida and Blastosporella zonata, are characterized by a large IR and enrichment of G4DNA. To determine whether high mitochondrial G4DNA content is common in fungi, we conducted the first broad survey of G4DNA content in fungal mtDNA, revealing it to be a highly variable trait. The results of this study provide important direction for future research on the function and evolution of G4DNA and organellar IRs.